Wireless power transmission of mobile robot for target tracking - Vaidyanathan Krithika; Murugan Nandhini; Chinnamuthu Subramani; Santhosh Rani Manoji Rao; Karpaga Meenakshi Sundaresan; Senthil Kiran Kumar; Hemadri Naresh (Institute of Advanced Engineering and Science, 2022)
The system is novel approach to combine wireless power transmission system (WPT) and automated guided vehicle (AGV). The wireless power transfer for charging the mobile robot is implemented using inductive coupling method. The system setup consists of transmitter coils whose switching action is controlled through transistors, receiver coil connected to full ridge rectifier and mobile robot. The track consists of number of transmitter coil which transmits power in form of electromagnetic waves. The receivers in the robot, which receives these waves and converts it back to electric power to charge the battery. The robot tracks its target destination based on the user command from the smart phone through Bluetooth. Very few theoretical researches are available on this field. A prototype was developed and tested based on the researches. The system achieves good range but falls short in efficiency to charge a battery, charging of battery takes longer time than regular charging time. Further research and extensive exploration can bring this technology from theory to practice.